Quality and Antioxidant Activity of Sweet Corn (Zea mays saccharata) Beverage Fermented with Lactobacillus plantarum B1765 - Aisyatin Fajriyah; Prima Retno Wikandari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Sweet corn (Zea mays saccharata) has potential as a functional food because it contains bioactive compounds, including phenolics and flavonoids, that contribute to its antioxidant activity. Fermentation with lactic acid bacteria is one method to increase the availability of these bioactive compounds. This study aimed to determine the effect of fermentation duration on the quality and antioxidant activity of a fermented sweet corn kernel juice beverage using Lactobacillus plantarum B1765. Fermentation was conducted for 0, 6, 12, 18, and 24 hours, with the following parameters measured: total Lactic Acid Bacteria (LAB), pH, total acid titration (TTA), total flavonoids, total phenolics, antioxidant activity, and organoleptic properties. The results showed that fermentation duration increased total LAB, TTA, total flavonoids, total phenolics, and antioxidant activity, while decreasing pH. The highest total LAB count was observed after 6 hours of fermentation, at 9.48 × 10? CFU/mL. After 24 hours of fermentation, total flavonoids increased from 2.2378 to 3.4635 mg QE/g and total phenolics from 3.0006 to 13.5678 mg GAE/g, accompanied by a decrease in the IC?? value from 333.8692 to 90.3687 ppm. A fermented sweet corn kernel juice beverage using L. plantarum B1765 has the potential to be developed as a functional food from locally sourced ingredients. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production